STRATEGI KOMUNIKASI RADIO VENUS FM MAKASSAR DALAM MENINGKATKAN DAYA TARIK PENDENGARNTYA - Audra Indah Lestari; Amaluddin Amaluddin; Muhammad Ilham (UNIVERSITAS MUSLIM INDONESIA, 2020)
The aims of this researcher are: (1) To find out how the Venus Fm Radio Communication Strategy Makassar in Increasing Listener Attractiveness. (2) To find out what are the obstacles faced by the Venus Fm Makassar Radio Communication Strategy in increasing the Attractiveness of its Listeners. This research lasted for one month. The type of research used in this thesis is descriptive qualitative method, the data in this study were obtained from primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. The data analysis technique is using qualitative data analysis. The results of this study indicate that the radio communication strategy of venus fm makassar in increasing the attractiveness of listeners is polite when speaking on the air, conveying relevant information, the language used is easy to understand. the program is made to suit the needs of listeners of radio venus and radio venus packs programs in an attractive manner every day updated according to the needs of listeners and broadcasts news with local content because local content is more popular with listeners. According to the target audience age 15-35 years. The strategy to be used must be considered selected and adapted to the goals of the organization or company. Radio Venus has 9 regular programs that are played from Monday to Saturday and has 12 special programs on Friday-Sunday. Barriers faced by Venus FM radio in Makassar in increasing the attractiveness of listeners From the obstacles above, namely from competition between media, namely good radio competition in programs owned and broadcasters owned. Radio Venus FM requires broadcasters to be able to do story telling, in order to make listeners feel comfortable and want to always listen to Radio Venus FM. Technical barriers are all obstacles, obstacles, and difficulties originating from supporting tools such as electronic devices and the internet and the existence of range limits and blocked networks if the electricity goes out.